A constrained modulus reconstruction technique for breast cancer assessment. - Samani, A.
A reconstruction technique for breast tissue elasticity modulus is described. This technique assumes that the geometry of normal and suspicious tissues is available from a contrast-enhanced magnetic resonance image. Furthermore, it is assumed that the modulus is constant throughout each tissue volume. The technique, which uses quasi-static strain data, is iterative where each iteration involves modulus updating followed by stress calculation. Breast mechanical stimulation is assumed to be done by two compressional rigid plates. As a result, stress is calculated using the finite element method based on the well-controlled boundary conditions of the compression plates. Using the calculated stress and the measured strain, modulus updating is done element-by-element based on Hooke's law. Breast tissue modulus reconstruction using simulated data and phantom modulus reconstruction using experimental data indicate that the technique is robust.
Keywords: Hooke's law; Breast cancer assessment; Breast tissue modulus reconstruction; Compression plates; Constrained modulus reconstruction technique; Finite element method; Medical diagnostic imaging; Normal tissues; Phantom modulus reconstruction; Quasi-static strain data; Stress calculation; Suspicious tissues; Well-controlled boundary conditions